Between-algorithm, between-individual differences in normal perimetric sensitivity: full threshold, FASTPAC, and SITA. Swedish Interactive Threshold algorithm - Wild, JM; Pacey, IE; Hancock, SA; Cunliffe, IA (Investigative ophthalmology & visual science, 1999)
To determine the between-algorithm differences in perimetric sensitivity for the Swedish Interactive Threshold algorithm (SITA) Standard, SITA Fast, FASTPAC, and Full Threshold algorithms; to determine the between-subject, between-algorithm differences in the magnitude of the normal variation in sensitivity. The sample comprised 50 normal subjects (mean age, 52.9 +/- 18.5 years) experienced in automated perimetry. One randomly assigned eye was examined at three visits with Program 30-2 of the Humphrey Field Analyzer (HFA). The first visit was a familiarization session. A two-period crossover design with order randomization within visits was used over the second and third visits. SITA Standard, SITA Fast, and HFA 640 Full Threshold were administered during one visit. FASTPAC and HFA 750 Full Threshold were administered during the remaining visit. Group mean Mean Sensitivity was 0.8 dB higher for SITA Standard than for Full Threshold (P < 0.001) and 1.3 dB higher for SITA Fast than for Full Threshold (P < 0.001). A similar trend was found between SITA and FASTPAC. The group mean Mean Sensitivity for SITA Fast was 0.5 dB higher than for SITA Standard (P < 0.001). The pointwise between-algorithm difference in sensitivity was similar for all algorithms. The pointwise between-algorithm, between-subject variability was lower for SITA. The examination durations for SITA Fast and SITA Standard were half those for FASTPAC and Full Threshold; SITA Fast was 41% that of SITA Standard (P < 0.001). SITA produced marginally higher mean mean sensitivity compared with that of existing algorithms and markedly reduced examination duration. The reduced between-subject variability of SITA should result in narrower confidence limits for definition of normality.